MEKANISME PENYELESAIAN SENGKETA PROSES CALON PERSEORANGAN PROVINSI DKI JAKARTA DALAM PEMILIHAN ANGGOTA DPD TAHUN 2024 - Vania Chairunnisa,; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
General elections as a means of realizing people's sovereignty have the potential for disputes, particularly electoral process disputes arising from decisions made by the General Elections Commission (KPU), Provincial KPU, and Regency/City KPU. The DKI Jakarta Province in the 2024 General Election is the region with the highest level of election vulnerability, one of which is marked by the emergence of procedural disputes in the stage of nominating independent candidates for the Regional Representative Council (DPD). This study aims to analyze the mechanism for resolving election process disputes involving independent candidates in DKI Jakarta Province in the 2024 DPD Member Elections. This study uses a qualitative methodology with a case study approach. Data was obtained through methods in-depth interviews with the Jakarta Provincial Election Supervisory Body (Bawaslu), the Jakarta Provincial General Election Commission (KPU), independent candidates, and legal representatives, and was supported by documentary studies. The research analysis uses the perspectives of Election Disputes, the Electoral Justice System, and Electoral Dispute Resolution (EDR). The results of the study show that the DKI Jakarta Provincial Bawaslu has resolved procedural disputes in accordance with the provisions of the law through a mediation and adjudication mechanism that is fast, simple, and free of charge. This mechanism is a formal method for resolving election procedural disputes that is carried out in accordance with the law and Bawaslu regulations. Process disputes are generally caused by differences in the interpretation of administrative requirements and voter support verification at the nomination stage. Although it has been carried out in accordance with the principles of electoral justice, its implementation still faces obstacles in the form of time constraints, administrative complexity, and uneven technical understanding among election participants. The conclusions drawn from this study highlight 11 requests for the settlement of election process disputes that were resolved through mediation and 1 request that was resolved through adjudication at the DKI Jakarta Provincial Bawaslu. The existence of a mechanism for settling election process disputes at Bawaslu has helped prevent problems from piling up at the Constitutional Court (MK). The recommendations provided consist of optimizing Silon, more thorough preparation and deeper understanding of candidacy and election process disputes for individual candidates in DKI Jakarta Province, improving the facilities and infrastructure of dispute resolution rooms, and adding competent human resources in the resolution of election process disputes at Bawaslu.